Activation of NLRP3 Inflammasome in the Skin of Patients with Systemic and Cutaneous Lupus Erythematosus - Katariina Mähönen; Annika Hau; Vincent Bondet; Darragh Duffy; Kari K. Eklund; Jaana Panelius; Annamari Ranki (Medical Journals Sweden, 2022)
NLRP3 inflammasome is suggested to contribute to the complex pathogenesis of systemic lupus erythematosus, but its role in cutaneous lupus erythematosus has not been addressed. This study investigated the expression of NLRP3 inflammasome components and levels of type I interferons in the skin of 20 patients with cutaneous lupus erythematosus. Expression of NLRP1/3, adaptor protein ASC (apoptosis-associated speck-like protein), caspase-1, interferon-α (IFN-α), myxovirus resistance protein (MxA), and interferon-induced proteins 1 and 2 (IFIT 1/2) in the skin was assessed using reverse transcription quantitative real-time PCR (RT-qPCR), western blotting and immunohistochemistry. Serum interferon-α protein levels from 12 patients were measured using digital enzyme-linked immunoassay (ELISA). Interleukin-1β expression was significantly upregulated in the lesional skin of patients with cutaneous lupus erythematosus compared with their uninvolved skin. However, NLRP1/3, ASC and caspase-1 were not significantly upregulated compared with the skin of control persons. IFN-α and IFN-induced proteins MxA and IFIT1/2 were strongly expressed in cutaneous lupus erythematosus skin. Variability in the expression of NLRP3 inflammasome components among patients suggests heterogeneity of pathological pathways in cutaneous lupus erythematosus.